Literacy in Reading and Writing: Systematic Literature Review - Farida Nugrahani; Wahyu Dini Septiari; Mukti Widayati (Edunity Kajian Ilmu Sosial dan Pendidikan, 2025)
The interest in reading and writing is the main foundation for improving individual literacy skills, which play an important role in the intellectual development of the community. This study aims to map the development of literacy in Indonesia using the Systematic Literature Review (SLR) method. A total of 1,500 relevant scientific articles from Google Scholar and Crossref (2014–2024) were analyzed with the help of the Publish or Perish application for metadata download and VOSviewer for data visualization. This study covers three main aspects: (1) literacy mapping based on education level (elementary to tertiary); (2) the grouping of literacy models used; and (3) identification of novelty in the literacy study approach. The results show a major focus on primary education, with the application of innovative methods such as digital literacy and project-based learning. The literacy models found vary, ranging from conventional to digital technology-based approaches. The analysis also reveals strong relationships between authors and specific study themes, visualized through networks of citations, author collaborations, and shared references. This mapping provides an in-depth overview of trends, focuses, and research gaps in literacy in Indonesia, serving as a basis for future research development. It offers comprehensive insights into trends, research foci, and identified gaps in Indonesian literacy research, thereby contributing to the theoretical foundation for evidence-based literacy policy development and establishing a bibliometric baseline for future systematic investigations in the Indonesian educational context.